RELATION BETWEEN HARDNESS OF (Ti, Al)N BASED MULTILAYERED COATINGS AND PERIODS OF THEIR STACKING - Mehdi Zaoui; Alexandre Bourceret; Yves Gaillard; Sylvain Giljean; Christophe Rousselot; Marie-José Pac; Fabrice Richard (Acta Polytechnica CTU Proceedings)
This study aims to model, by using a finite element method, the relationship between the hardness and the period Λ of metal/nitride multilayer coatings (Ti0.54Al0.46/Ti0.54Al0.46N)n in order to understand the increase of the hardness at the low periods [1] and then optimise the multilayer coating architecture to obtain the best mechanical properties. A 2D axisymmetric finite element model of the Berkovich nanoindentation test was developed. The coating was designed as a stacking of Ti0.54Al0.46 and Ti0.54Al0.46N nanolayers with, in the first hypothesis, equal thickness and perfect interface. The elastoplastic behaviours of the metal and nitride layers were identified by Berkovich nanoindentation experiments and inverse analysis on thick monolayer samples. The indentation curves (P-h) obtained by this model depend on the period Λ of the stacking. Simulated (P-h) curves were compared with experimental data on 2 μm thick films with different periods Λ ranging from 10 to 50 nm deposited by RF magnetron sputtering using reactive gas pulsing process (RGPP). The model forecasts are very consistent with the experience for the largest period but the model does not reproduce the hardness increase at the lowest periods. The Λ = 10 nm coating was analysed by electron energy loss spectroscopy (EELS) on a transmission electron microscope. Results show intermixing of the layers with the presence of nitrogen atoms in the metal layer over a few nanometers [1]. It was concluded that the metal/ceramic interface plays an important role at low periods. The addition in the model of a transition layer in the metal/nitride stacking, with an elastoplastic metal/ceramic medium behaviour, allows to reproduce the nanoindentation experimental curves. The thickness of this transition layer deduced from model updating method is in very good agreement with EELS observations.